Factors affecting management accounting and control systems. A critical review of empirical studies - Joanna Dyczkowska (Zeszyty Teoretyczne Rachunkowości, 2015)
Knowledge of management accounting & control systems and factors which may affect the design of such systems has become crucial due to emerging changes both in the external and internal business environment. Therefore it is necessary to conduct comprehensive, long-term basic research in order to prove previously formulated hypotheses in new conditions and fulfil the research gap. Based on critical review of empirical studies published in prestigious scientific journals this paper aims at validating the assumed hypotheses and at generalising research findings on impacts of various determinants on man-agement accounting & control systems. The predominant contingent factors include: type of strategy implemented, national culture, perceived environment uncertainty and integrated information system.